Evaluating the purchasing intentions of retailers towards cement blenders in Gauteng - Koopedi, Neo (University of the Witwatersrand, Johannesburg, 2024)
The study investigates the purchasing intentions of retailers towards cement blenders in Gauteng. The study made use of a quantitative research design, utilizing Slovin’s formula to determine the sample size. The gathering of data was conducted via a self-administered online survey which yielded 203 valid responses. The data from the survey was evaluated using various descriptive statistics, hypothesis testing and structural equation modelling. The research objectives were achieved through a quantitative analysis of the survey responses from retail store managers and owners. The major constructs measured were price, brand image, product quality and their influence on purchase intention as the dependent variable. Hypothesis testing was subsequently conducted to explore the relationship between the key variables. The outcomes of the study revealed that brand image and product quality had significantly positive effects on purchase intention, supporting their respective hypotheses along with academic literature. Contrary to scholarly findings, price demonstrated a weak relationship with purchase intention. The hypothesis testing for resulted in a high p-value, suggesting that price was not a significant factor shaping purchase intentions. This suggests that other factors may overshadow price when retail store owners and managers purchase blended cement. These outcomes provide insights on the factors propelling consumer behaviour and the importance of product quality and brand image driving purchase intention in the context of blended cement.
A research report submitted in fulfillment of the requirements for the Master of Business Administration, in the Faculty of Commerce Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Cement blenders; purchase intention; product quality; SDG-9: Industry, innovation and infrastructure; SDG-8: Decent work and economic growth